P723 Effectiveness and persistence of vedolizumab in patients with Inflammatory bowel Disease: Results from the Belgian REal-LIfe study with VEdolizumab (Be-RELIVE). (16th January 2018) - Reenaers, C; Cremer, A; Dewit, O; de Vroey, B; Van Moerkercke, W; Bossuyt, P; Muls, V; Imschoot, J; Block, S; Hantson, A; Van Hootegem, P
Abstract: Background: Vedolizumab (VDZ) was efficacious in inducing and maintaining remission in Crohn's disease (CD) and ulcerative colitis (UC) in the Phase III GEMINI studies. This retrospective study assessed effectiveness and treatment persistence of VDZ in a Belgian real-world cohort of patients with CD or UC, including more than 25% of biologic-naïve patients. Methods: CD and UC patients who started VDZ between 01/09/2015 and 31/07/2016 and who attended at least 1 visit after first infusion were included from 15 Belgian centres. Data were collected at baseline (before first infusion), week (W)10, W14 (CD patients only), and month (M)6. Last data were collected in January 2017. Treatment response and remission rates were assessed based on the changes in disease activity scores. Data analyses were performed according to disease type (UC/CD), and further stratified by treatment history (biologic-naïve/failure patients). Treatment persistence was assessed using Kaplan–Meier analysis. Adverse events (AEs) recorded in patients' files were collected. Results: Of the 418 patients who started VDZ (safety population), 325 (202 CD and 123 UC) eligible patients were included in data analyses (effectiveness population). 22.2% of UC and 34.2% of CD patients were biologic-naïve. About three-quarters of the patients achieved clinical response at W10/W14 (CD: 71.4%; UC: 77.2%) that persisted up to M6 (CD: 75.6%; UC: 83.9%). At M6, 66.7% of CD patients were in remission; the response and remission rates were numerically higher among biologic-naïve patients (UC, respectively, additional 9% and 24%; CD, additional 22% and 35.8%) (Table 2) .At M6, 87.6% of CD and 86.1% of UC patients were still on VDZ treatment. For 7.7% of patients, VDZ dose was escalated to every 4W. The most common AEs ( n = 418) were arthralgia (3.8%), fatigue (3.6%), skin eruption (3.1%), headache (2.9%) and gastroenteritis (2.6%). Conclusions: After 6 months of treatment with VDZ, about 85% of patients were still on treatment, of whom more than 40% achieved remission. Treatment effectiveness appeared higher in biologic-naïve compared with biologic-failure patients. No new safety signals were raised. These results are consistent with findings from the Phase III and real-world evidence studies with VDZ.